Study on immobilization of nitrogen and phosphorus in sediments using modified fly ash composite material. (29th March 2022) - Zou, Jiale; Sun, Rongqiang; Zhu, Zhaoliang; Zhou, Hao; Ji, Xinyu
Abstract: In this paper, a new type of particle-modified fly ash composite material was prepared using fly ash as the main raw material, which could immobilize nitrogen and phosphorus pollutants in sediment and control its release into water. Preliminary modification of fly ash was achieved by soaking in NaOH and calcining at high temperature of CaO. The modified fly ash was mixed with four auxiliary materials, namely cement, slag, water glass and quartz sand, and was formed after 14 days of curing. X-ray diffraction (XRD) and scanning electron microscope-energy dispersive spectrometer (SEM-EDS) were used to examine the material microstructure, element composition, crystal mineral changes, and also to further examine the physical indicators and mechanical properties of the material. In the end, we chose to use modified fly ash composite 10% cement to make granular modified fly ash composite materials. Taking the actual polluted river sediment as the research object, a 22-day coverage effect experiment was carried out, and it was finally found that the 2 cm-thick modified fly ash composite material cover layer inhibited the ammonia nitrogen (NH4 + -N)、total nitrogen (TN) and total phosphorus (TP) of the sediments at 90.91%, 75.06% and 90.63%, respectively. This confirms that it is a material with good performance and practical application value. HIGHLIGHTS: Realized the composite of multiple materials. The microscopic characterization and crystal phase of the material are analyzed in detail. Provide mechanical and physical indicators of materials. Carried out the practical application experiment of sediment pollutant suppression. It is a granular fly ash material with low cost, small particle size, high strength and good adsorption. Graphical Abstract